Improvement of Energy Efficiency of Dehydration Processes in the Conditions of Selective Supply of Electromagnetic Energy - Burdo O.G.; Levitsky A.P.; Sirotyuk I.V.; Burdo A.K.; Kepin N.I.; Petrovsky V.V.; Yevtushenko I.N. (Problems of the Regional Energetics, 2025)
An analysis of conventional dehydration processes used in food technologies—evaporation and drying—has been conducted, and their key challenges have been identified. The global research experience in dehydration technologies based on innovative microwave energy sources is reviewed. The studies carried out indicate that dehydration in an electromagnetic field holds clear promise both in terms of reducing energy consumption and improving the quality of the final product. At the same time, the existing research has been conducted using laboratory-scale setups; comprehensive studies and engineering design methods for electrodynamic—type equipment are lacking. The aim of this work is to develop the scientific foundations of dehydration processes under conditions of selective electromagnetic energy supply, to formulate design methods for continuous—flow dehydrators, and to create and test an experimental prototype of an electrodynamic dehydrator. To achieve the stated goal, the authors have synthesized previous research—where they hold priority—and formulated a hypothesis for the creation of apparatuses that address the scientific and technical contradictions inherent in traditional technologies. It is demonstrated that, under selective energy supply conditions, solutions can be concentrated within a single unit. The paper analyzes transformation schemes within the dehydrator, a parametric model, and the design of the experimental prototype. Results on the quality of obtained concentrates are provided. The most important outcome of the work is the development of theoretical foundations for dehydration in a microwave field, yielding high-quality concentrates. The significance of the study lies in the creation of an energy—efficient electrodynamic unit that replaces conventional evaporators and dryers.